Novel Putative Effectors Identified in the Arrhythmogenesis of Idiopathic Outflow Tract Ventricular Arrhythmias A Novel Concept Beyond Triggered Activity - Géczy Tamás (JOURNAL OF CLINICAL MEDICINE, 2025)
Background: The arrhythmogenic mechanism of idiopathic ventricular arrhythmias (VAs) from the outflow tracts (OTs) and adjacent anatomical structures has been described to be triggered activity. However, it is incompletely understood why this focal mechanism mainly originates from the OTs and what factors could precipitate it. The aim of this study was to further elucidate the arrhythmogenic mechanisms underlying focal ventricular arrhythmias originating from the outflow tracts. Methods: Six patients referred for catheter ablation of OT-related PVCs were included in this study. Programmed atrial stimulation at the interatrial septum or within the coronary sinus was performed. Pacing at the AV annuli was capable of evoking OT-PVCs with an ECG morphology identical to clinical PVCs by presumably capturing specific fibers within the network of nodal-type tissue of the AV junctional sleeves. Results: Based on the analysis of intracardiac electrograms, the observed PVCs could indeed be elicited as a result of prior atrial stimulation. Conclusions: Our findings suggest that unique pathways might exist between specific periannular atrial locations and the OTs, the activation of which could result in triggering PVCs from the presumed “exit site” of these pathways in the OTs. These findings might facilitate the development of a novel ablation strategy, which might also include the mapping of atrial locations, in order to identify and ablate the presumed “entry sites” of these special pathways.